Improvement of Stability and Anticancer Activity of Chlorambucil‐Tetrapeptide Conjugate Vesicles. Issue 6 (29th March 2016) - Zhang, Wei; Zhu, Wenjun; He, Ruiyu; Fang, Shuo; Zhang, Yemin; Yao, Chen; Ismail, Muhammad; Li, Xinsong
Abstract: Chlorambucil is a classic nitrogen mustard drug that has been used in the treatment of cancers. It may induce neutropenia, thrombocytopenia and other side effects because of its short lifetime and off‐target effect. In this report, chlorambucil‐tetrapeptide (AAAK, A3 K) conjugate vesicles were developed to improve the stability and bioactivity of chlorambucil. First of all, chlorambucil‐A3 K conjugate was synthesized by solid phase synthesis strategy. Secondly, the chlorambucil‐A3 K conjugate was assembled and characterized by critical aggregation concentration, circular dichroism, dynamic light scattering and transmission electron microscopy. The results indicated that the chlorambucil‐A3 K conjugate can be assembled to form spherical vesicles with an average diameter of 390.5 nm, and high drug loading about 47.1% is reached. Surprisingly, the preliminary biological evaluation of the chlorambucil‐A3 K conjugate vesicles revealed the best in vitro anticancer activity against HeLa, HepG‐2 and MCF‐7 cell lines compared with chlorambucil and chlorambucil‐A3 K conjugate free drugs. Furthermore, conjugate vesicles showed excellent in vivo antitumoral activity. It can be partly attributed to their vesicular structure which isolates chlorambucil active moiety from aqueous solution to retard degradation before killing cancer cells. Therefore, chlorambucil‐peptide (A3 K) conjugate vesicles may be an alternative delivery system of chlorambucil. Abstract : Formation of vesicles by self‐assembly of chlorambucil‐tetrapeptide conjugate.